Dual protective role of velutin against articular cartilage degeneration and subchondral bone loss via the p38 signaling pathway in murine osteoarthritis - Wang, Kelei; Lu, Xuanyuan; Li, Xinyu; Zhang, Yufeng; Xu, Rongjian; Lou, Yun; Wang, Yanben; Zhang, Tan; Qian, Yu (Frontiers in Endocrinology, 2022)
Osteoarthritis (OA) is a common degenerative joint condition associated with inflammation and characterized by progressive degradation of the articular cartilage and subchondral bone loss in the early stages. Inflammation is closely associated with these two major pathophysiological changes in OA. Velutin, a flavonoid family member, reportedly exerts anti-inflammatory effects. However, the therapeutic effects of velutin in OA have not yet been characterized. In this study, we explore the effects of velutin in an OA mouse model. Histological staining and micro-CT revealed that velutin had a protective effect against cartilage degradation and subchondral bone loss in an OA mouse model generated by surgical destabilization of the medial meniscus (DMM). Additionally, velutin rescued IL-1β-induced inflammation in chondrocytes and inhibited RANKL-induced osteoclast formation and bone resorption in vitro. Mechanistically, the p38 signaling pathway was found to be implicated in the inhibitory effects of velutin. Our study reveals the dual protective effects of velutin against cartilage degradation and subchondral bone loss by inhibiting the p38 signaling pathway, thereby highlighting velutin as an alternative treatment for OA.